FirstAct for Efficacy in ACCase-Tolerant Grain Sorghum - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective of this study was to compare FirstAct with several tank mix partners for efficacy in herbicide-tolerant grain sorghum. FirstAct (quizalofop) alone or in tank mixtures controlled Johnsongrass 94% or more. However, tank mixing FirstAct with any broadleaf herbicide was generally antagonistic to Palmer amaranth control. Minor sorghum injury was 5% or less by four weeks after postemergence treatment. Sorghum yields increased with all postemergence treatments except with atrazine alone.
Keywords: ACCase-resistant sorghum; Double Team sorghum; grain sorghum